TURISMO, DESENVOLVIMENTO LOCAL/REGIONAL E SUSTENTABILIDADE: ESTUDO DE CASO DO PROJETO TAMAR EM PRAIA DO FORTE - BAHIA - Brito, Vivian Costa (2008)
Tourism, as a social and economic activity, uses as its basic resources the environment and fragile ecosystems that are usually observed in costal areas. Its impacts raise many questions and, to answer that, a deep analysis is required, regarding the territorial development. Endogenous and exogenous factors in this context are the basis to understand the local and regional dynamic of the effects of TAMAR Project in Praia do Forte that works together with the tourism activity in the region and to the network formed in its social and economic area of influence. The central issue that motivates this case study is to know if the articulation of TAMAR Project with the tourism activity leads to a local and regional touristic development, attached to sustainable practices. As the main theoretical basis in this analysis, the growth and development economic models will set the base to understand the type of the dynamic between TAMAR Project and tourism in Praia do Forte. This dissertation is an exploratory case study with quantitative and qualitative procedures, beginning with the accomplishment of focal groups with the local community and the application of forms to tourists and locals, as well as interviews with the other stakeholders. The results point to many different types of conflicts in Praia do Forte that are mainly a consequence of the development of land ventures focused on tourism, second home or business, because they create competition with the inns owners, and also alter the landscape of the region, uncharacterizing the fishing village and taking over the spaces of the existing natural resources. Tourism and TAMAR project coexist but they don t have cooperation activities aimed to the qualification of the tourist product of Praia do Forte. Visitors to the TAMAR mostly no not produce effects on the local economy, unlike the tourists who stay in Praia do Forte. The expansion of the multiplier effect that the TAMAR project leaves to the community is limited, because visitors basically consume into its own shop, and also there is no encouraging to the formation of productive chains in the region. Otherwise, the local / regional development could not be verified, because there is a large concentration of resources in the big enterprises, hotel chains and commerce and the community is put aside of this process. It is also important to emphasize that the tourism product sold in Praia do Forte has a strong Ecotourism appeal. However, many actions or structures are not consistent with the standards of low impact and control over visitation, specially related to the TAMAR Project.